2011
DOI: 10.1007/s11357-011-9328-z
|View full text |Cite
|
Sign up to set email alerts
|

Androgen depletion in humans leads to cavernous tissue reorganization and upregulation of Sirt1–eNOS axis

Abstract: Aging and physiological androgen decay leads to structural changes in corpus cavernosum (CC) that associate with erectile function impairment. There is evidence that such changes relate to nitric oxide (NO) bioavailability, an endothelial compound produced by the action of endothelial NO synthase (eNOS), and is regulated by sirtuin-1 (Sirt1), a NAD + -dependent protein deacetylase. Taking into account the reduced NO synthesis observed in aging and erectile dysfunction, we aimed to characterize human CC of andr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
23
1
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 73 publications
5
23
1
1
Order By: Relevance
“…Alternatively, the SMC content increase itself could be responsible for the increase of Sirt1 59. Once again, this finding aligns with features observed in 6-month old ER rats which also exhibit an increase in the SM layer compared with high-fat diet-treated counterparts 77.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Alternatively, the SMC content increase itself could be responsible for the increase of Sirt1 59. Once again, this finding aligns with features observed in 6-month old ER rats which also exhibit an increase in the SM layer compared with high-fat diet-treated counterparts 77.…”
Section: Discussionsupporting
confidence: 85%
“…Additional differences were observed in the effects induced by the treatments with these beverages, as green tea48 but not red wine49 consumption strongly decreases the blood levels of total testosterone. Although we reported no noticeable cavernous structural modifications in green tea-treated rats,48 other studies have demonstrated an association between hypogonadism and a decrease in cavernous NO synthesis,57 an increase in ED prevalence in MS patients58 and a shift in the cellular proportion in cavernous tissue similar to natural aging 59. In fact, androgen chemical deprivation of young men induces a decrease in SM content in cavernous tissue coupled with an increase in connective tissue content, which is a pattern similar to that observed in chronological aging.…”
Section: Discussioncontrasting
confidence: 55%
“…These changes appear to parallel previous human observations that recently attracted more attention, not only concerning sexual performance, but in a wider context of male health. That is so because experimental research supports the point that testosterone deficiency profoundly affects angioarchitecture of cavernous tissue and impairs the erectile capacity (Tomada et al 2011;Traish et al 2007) and also because hypogonadism associates with MetS and is a risk factor for CVD (Jones 2007;Frederiksen et al 2012;Laughlin et al 2008;Vikan et al 2009). …”
Section: Discussionmentioning
confidence: 97%
“…The meaning is uncertain, especially when it is compared with the SMC density at the tail artery, a muscular vessel widely used in the study of vascular SM (Leal et al 2008), whose age-related features under controlled and dietary experimental conditions are here described for the first time. Loss of SMC and increment of CT deposition along aging have been repeatedly reported in corporal tissue either in animal models (Burchard et al 2000;Carrier et al 1997) and humans (Tomada et al 2011). These changes provoke mechanical alterations of the penis, as reduction in its elasticity and compliance, which lead to erectile function impairment (Ferrini et al 2009).…”
Section: Discussionmentioning
confidence: 97%
“…Bij mannen die voorafgaand aan transgenderchirurgie androgeendeprivatietherapie ondergaan, en bij mannen met hypogonadisme treedt een significante afname op van de gladde spiercellen en een toename van collageen in de corpora cavernosa [42]. Maar de moleculaire mechanismen hierachter worden niet goed begrepen.…”
Section: Testosteron En Edunclassified